2020
DOI: 10.1002/ecy.3145
|View full text |Cite
|
Sign up to set email alerts
|

Diverging responses to threats across generations in zooplankton

Abstract: Our understanding on how organisms evolutionarily cope with simultaneously occurring, multiple threats over generations is still elusive. In a long‐term experimental study, we therefore exposed clones of a freshwater cladoceran, Daphnia magna, to threats from predation and ultraviolet radiation (UVR) during three consecutive parthenogenetic generations. We show that Daphnia can adapt to different sets of threats within three generations through modifying morphology, swimming behavior, or life‐history traits. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 55 publications
(77 reference statements)
4
18
1
Order By: Relevance
“…Their behavioral response consists in the increase of their swimming speed and distancing from the UVR source (Ekvall et al., 2015). Recent studies have shown that the swimming speed and behavior under UVR threat are inherited in D. magna across generations (Sha et al., 2020, this study). Moreover, the present study highlights a significant difference in swimming speed between populations under threat.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Their behavioral response consists in the increase of their swimming speed and distancing from the UVR source (Ekvall et al., 2015). Recent studies have shown that the swimming speed and behavior under UVR threat are inherited in D. magna across generations (Sha et al., 2020, this study). Moreover, the present study highlights a significant difference in swimming speed between populations under threat.…”
Section: Discussionmentioning
confidence: 50%
“…Sha et al. (2020) further demonstrated that D . magna adaption to different threats (predation, UVR) occurred within three generations.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations